Key characteristics of successful quality improvement curricula in physician education: a realist review. Issue 1 (30th September 2014) - Jones, Anne C; Shipman, Scott A; Ogrinc, Greg
Abstract : Purpose: Quality improvement (QI) is a common competency that must be taught in all physician training programmes, yet, there is no clear best approach to teach this content in clinical settings. We conducted a realist systematic review of the existing literature in QI curricula within the clinical setting, highlighting examples of trainees learning QI by doing QI. Method: Candidate theories describing successful QI curricula were articulated a priori . We searched MEDLINE (1 January 2000 to 12 March 2013), the Cochrane Library (2013) and Web of Science (15 March 2013) and reviewed references of prior systematic reviews. Inclusion criteria included study design, setting, population, interventions, clinical and educational outcomes. The data abstraction tool included categories for setting, population, intervention, outcomes and qualitative comments. Themes were iteratively developed and synthesised using realist review methodology. A methodological quality tool assessed the biases, confounders, secular trends, reporting and study quality. Results: Among 39 studies, most were before–after design with resident physicians as the primary population. Twenty-one described clinical interventions and 18 described educational interventions with a mean intervention length of 6.58 (SD=9.16) months. Twenty-eight reported successful clinical improvements; no studies reported clinical outcomes that worsened. Characteristics of successful clinical QI curricula include attention to the interface of educational and clinical systems, careful choice of QI work for the trainees and appropriately trained local faculty. Conclusions: This realist review identified success characteristics to guide training programmes, medical schools, faculty, trainees, accrediting organisations and funders to further develop educational and improvement resources in QI educational programmes.